Antepartum Mastitis - Cheng-Shing Kuo; Hun-Shan Pan; Jiann-Loung Hwang (Elsevier, 2004)
Objective: Parenchymatous infection of the mammary glands is a rare antepartum complication but is occasionally observed during the puerperium and lactation. We report a case of antepartum mastitis with severe abscess formation and successful treatment using semicircular incisions and drainage. Case Report: A 24-year-old primigravid woman had a 36-week pregnancy with mastitis and had been treated with cephalexin monohydrate for 7 days. Two weeks later, the superior medial quadrant of the right breast developed abscesses. The patient received surgical drainage after vaginal delivery of a male infant. She was discharged on the fifth hospital day with an open cavity packed with gauze. Conclusion: Antepartum mastitis is uncommon during pregnancy. Physicians should assume that early, aggressive treatment of this infectious process will maximize breast tissue conservation and function. When abscess formation occurs, surgical drainage is essential, and general anesthesia is usually required.